Carbon-silicon / carbon composite materials and their preparation methods

CN122953210APending Publication Date: 2026-10-20HANWHA SOLUTIONS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480082688.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-29
Filing Date
2024-12-18
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,硅具有下述问题:即在充电和放电期间其体积增加高达约300%,使得其机械稳定性非常差,因为作为负极活性材料的硅随着充电和放电的进行而断裂

Benefits of technology

在根据本发明实施方式的碳-硅/碳复合材料中,通过在多孔碳载体的表面上和/或孔内形成硅/碳复合基质,其中,相对于总孔,该多孔碳载体具有高的中孔比例,当将碳-硅/碳复合材料用作负极活性材料时,能够抑制整体硅尺寸,并且能够抑制晶体-LixSiy(例如Li15Si4或Li3.75Si)的形成,从而缓解重复充放电过程中电池性能劣化,其中,晶体-LixSiy是导致电池性能劣化的中间相。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a carbon-silicon / carbon composite material and its preparation method, wherein a silicon / carbon composite matrix is ​​formed on the surface and within the pores of a porous carbon support with controlled pore characteristics. When the carbon-silicon / carbon composite material according to embodiments of the present invention is used as a negative electrode active material, it can suppress the overall silicon size and suppress crystalline Li- x Si y (e.g. Li) 15 Si4 or Li 3.75 The formation of Si) alleviates the degradation of battery performance during repeated charge and discharge processes, among which, crystalline Li x Si y It is an intermediate phase that leads to the degradation of battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to carbon-silicon / carbon composite materials, and more specifically, to carbon-silicon / carbon composite materials and methods for their preparation. Background Technology

[0002] Carbon materials are materials composed of carbon, one of the most abundant resources on Earth. They are key materials widely used in hydrogen fuel cell vehicles, aerospace, rechargeable batteries, and high-end consumer products because they are very lightweight, high-strength, and possess excellent electrical and thermal conductivity.

[0003] Carbon materials can be manufactured from various raw materials such as coconut shells, polyacrylonitrile, rayon, and pitch. Among these, carbon materials made from solid raw materials such as coconut shells are difficult to control in terms of molecular weight and composition (Korean Patent Application Publication No. 10-2019-0093960).

[0004] In contrast, bitumen, as a viscoelastic solid polymer extracted from crude oil or plants, has the following advantages: when converted into carbon materials, bitumen offers high yields, is inexpensive, and its molecular structure is closer to that of graphite than other raw materials, thereby reducing the energy required for heat treatment (US Patent Nos. 4,242,196 and 4,340,464).

[0005] In particular, pyrolysis fuel oil (PFO), naphtha cracking bottom oil (NCB), vacuum residue (VR), and fluidized catalytic cracking decanter oil (FCC-DO), which are obtained as byproducts in the petroleum refining process, have high content of aromatic compounds and low content of impurities such as sulfur and nitrogen. Therefore, asphalt made from them has attracted much attention as a raw material for carbon materials.

[0006] Meanwhile, in order to improve the capacity of secondary batteries, silicon-based anode active materials were explored. Silicon has an extremely high theoretical energy density, and therefore has attracted much attention as a next-generation battery anode active material that can replace graphite. However, silicon has the following problem: its volume increases by up to about 300% during charging and discharging, resulting in very poor mechanical stability, because silicon, as an anode active material, breaks down during charging and discharging.

[0007] Therefore, many studies have been conducted to solve these problems, but existing anode active materials still have not fully solved the problem of fracture caused by volume expansion.

[0008] [Existing Technical Documents] [Patent Literature] (Patent Document 0001) Korean Patent Publication No. 10-2019-0093960 (Patent Document 0002) US Patent No. 4,242,196 (Patent Document 0003) US Patent No. 4,340,464 Summary of the Invention Technical issues The present invention relates to a carbon-silicon / carbon composite material, wherein a silicon / carbon composite matrix is ​​formed within and / or on the surface of a porous carbon support having controlled pore characteristics.

[0009] The present invention also relates to a method for preparing carbon-silicon / carbon composite materials.

[0010] The present invention also relates to providing a negative electrode active material, which includes a carbon-silicon / carbon composite material.

[0011] Technical solution The present invention provides a carbon-silicon / carbon composite material comprising: a porous carbon support having a mesopore volume ratio of 5% to 80% based on the total pore volume, wherein the mesopores have a pore size of 2 nm to 50 nm; and a silicon / carbon composite matrix disposed on the surface and within the pores of the porous carbon support.

[0012] According to one embodiment of the present invention, the porous carbon support may have a density of 300 μm. 2 / g to 3000m 2 BET specific surface area per g, tap density from 0.05 g / mL to 0.5 g / mL, and average particle size from 1 μm to 20 μm.

[0013] In addition, based on the total weight of the carbon-silicon / carbon composite material, the silicon content can be between 20 and 70% by weight.

[0014] Furthermore, based on the total weight of the carbon-silicon / carbon composite material, the silicon / carbon composite matrix can be present in an amount ranging from 10% to 90% by weight.

[0015] In addition, the average size of silicon crystals in the silicon / carbon composite matrix can be 10 nm or smaller.

[0016] In addition, the carbon-silicon / carbon composite material has a c / a peak ratio of 0 to 1.5.

[0017] In addition, the present invention provides a method for preparing carbon-silicon / carbon composite materials, the method comprising forming a silicon / carbon composite matrix on the surface and within the pores of a porous carbon support to prepare the carbon-silicon / carbon composite material.

[0018] According to one embodiment of the present invention, before preparing the carbon-silicon / carbon composite material, the method may further include: (1) synthesizing asphalt by pyrolysis and polycondensation of petroleum-based raw materials; (2) curing and granulating the asphalt to obtain granular asphalt, or curing, granulating and pulverizing the asphalt to obtain powdered asphalt; (3) stabilizing the granular asphalt or powdered asphalt; (4) carbonizing the stabilized asphalt to obtain carbonized products; and (5) activating the carbonized products to obtain porous carbon carriers.

[0019] In addition, silicon / carbon composite matrices can be formed by composite CVD of silicon and carbon sources on a porous carbon support.

[0020] In addition, the gas flow ratio of silicon source to carbon source can be from 1:0.1 to 1:2.

[0021] In addition, the present invention provides a negative electrode active material comprising the above-mentioned carbon-silicon / carbon composite material.

[0022] In addition, the present invention provides an all-solid-state battery, which includes a solid electrolyte interphase (SEI) layer, the SEI layer comprising the aforementioned carbon-silicon / carbon composite material.

[0023] Beneficial effects In the carbon-silicon / carbon composite material according to embodiments of the present invention, a silicon / carbon composite matrix is ​​formed on the surface and / or within the pores of a porous carbon support, wherein the porous carbon support has a high proportion of mesopores relative to the total pore size. When the carbon-silicon / carbon composite material is used as a negative electrode active material, the overall silicon size can be suppressed, and crystalline Li- x Si y (e.g. Li) 15 Si4 or Li 3.75 The formation of Si) mitigates battery performance degradation during repeated charge and discharge processes, among which crystalline Li x Si y It is an intermediate phase that leads to the degradation of battery performance.

[0024] Furthermore, the preparation method according to embodiments of the present invention can easily prepare carbon-silicon / carbon composite materials with the above-mentioned properties. Attached Figure Description

[0025] Figure 1 This is a SEM image of a carbon-silicon / carbon composite material (Example 1) according to an embodiment of the present invention.

[0026] Figure 2 The graphs show the electrochemical evaluation results of Examples 1, 2 and Comparative Example 1 of the present invention, namely, charge-discharge efficiency, ICE and capacity retention.

[0027] Figure 3 This is a graph showing the dQ / dV measurement results of Embodiment 1, Embodiment 2 and Comparative Example 1 of the present invention.

[0028] Figure 4 This is an image showing the XRD analysis results of a carbon-silicon / carbon composite material (Example 1) according to one embodiment of the present invention.

[0029] Figure 5 These are images showing the XRD analysis results of carbon-silicon / carbon composite materials of comparative examples and Example 1 according to an embodiment of the present invention at different heat treatment temperatures (Examples 1-1 to 1-3). Detailed Implementation

[0030] This invention is not limited to the embodiments disclosed below. Various modifications can be made as long as the spirit of this invention is not changed.

[0031] In this specification, unless otherwise stated, the terms "comprising" or "including" mean that other components may be further included.

[0032] Unless otherwise stated, all numerical values ​​and wording describing the amounts of components, reaction conditions, etc., described herein should be understood in all cases to be modified by the term “about”.

[0033] The present invention will now be described in more detail.

[0034] Carbon-silicon / carbon composite materials According to one embodiment of the present invention, a carbon-silicon / carbon composite material is provided, comprising: a porous carbon support and a silicon / carbon composite matrix, wherein the porous carbon support has a mesopore volume ratio of 5% to 80% based on the total pore volume, wherein the mesopores have a pore size of 2 nm to 50 nm; wherein the silicon / carbon composite matrix is ​​disposed on the surface and within the pores of the porous carbon support.

[0035] The components of a carbon-silicon / carbon composite material according to one embodiment of the present invention will be described below.

[0036] Porous carbon support The carbon-silicon / carbon composite material according to one embodiment of the present invention comprises a porous carbon support.

[0037] Based on the total pore volume, the porous carbon support can have a mesopore volume ratio of 5% to 80%, preferably 30% to 60%, and more preferably 40% to 50%, wherein the pore size of the mesopores is 2 nm to 50 nm. If the mesopore volume ratio in the porous carbon support is less than 5%, the excessive number of micropores may cause the silicon / carbon composite matrix to form relatively extensively on the outside of the particles, and if the mesopore volume ratio in the porous carbon support exceeds 80%, the hardness of the particles may be insufficient, and therefore the structure of the electrode may collapse when it is used to manufacture electrodes.

[0038] Furthermore, porous carbon supports can have a diameter of 300 to 3000 μm. 2 The BET specific surface area is 300 to 1500 m² / g. Preferably, the porous carbon support can have a BET specific surface area of ​​300 to 1500 m² / g. 2 / g, more preferably 500 to 1500m 2 / g BET specific surface area. If the BET specific surface area of ​​the porous carbon support is less than 300m². 2 If the number of macropores exceeds 3000 m² / g, then an excessive number of macropores may lead to an insufficient number of effective pores, and if the BET specific surface area of ​​the porous carbon support exceeds 3000 m² / g... 2 If the number of micropores is too large, the silicon / carbon composite matrix may be deposited relatively extensively on the outside of the particles.

[0039] Additionally, the porous carbon support can have a tap density of 0.05 to 0.5 g / mL. Preferably, the porous carbon support can have a tap density of 0.05 to 0.3 g / mL, more preferably 0.1 to 0.3 g / mL. If the tap density of the porous carbon support is less than 0.05 g / mL, the process may be difficult to control during the formation of the silicon / carbon composite matrix, thus the yield may be reduced. Furthermore, if the tap density of the porous carbon support exceeds 0.5 g / mL, it may be difficult to uniformly form the matrix during the formation of the silicon / carbon composite matrix.

[0040] Furthermore, the porous carbon support can have an average particle size of 1 to 20 μm. Preferably, the porous carbon support can have an average particle size of 3 to 20 μm, more preferably 3 to 10 μm. If the average particle size of the porous carbon support is less than 1 μm, the silicon / carbon composite matrix cannot fully penetrate into the pores, and most of it is only formed on the outside of the particles. If the average particle size of the porous carbon support exceeds 20 μm, it is difficult to fully form a silicon / carbon composite matrix inside the pores.

[0041] The carbon-silicon / carbon composite material according to one embodiment of the present invention includes a porous carbon support having the above-mentioned properties. Therefore, when the carbon-silicon / carbon composite material is used as a negative electrode active material, it has excellent conductivity and can alleviate the stress caused by the volume expansion of silicon.

[0042] Silicon / carbon composite matrix According to one embodiment of the present invention, a carbon-silicon / carbon composite material comprises a silicon / carbon composite matrix disposed on the surface and within the pores of a porous carbon support.

[0043] In this invention, the silicon / carbon composite matrix can refer to a continuous phase in which silicon portions formed by Si-Si bonds and silicon carbide portions formed by Si-C bonds coexist (Si... x C y ).

[0044] In a specific embodiment of the present invention, as described below, carbon-silicon / carbon composite materials can be obtained by performing composite CVD of silicon and carbon sources on a porous carbon support.

[0045] In a specific embodiment of the present invention, the silicon / carbon composite matrix may include crystalline silicon particles. In this case, the size of the silicon crystals can be on the nanometer scale. Specifically, the average size of the silicon crystals in the silicon / carbon composite matrix can be 10 nm or less. Preferably, the average size of the silicon crystals in the silicon / carbon composite matrix can be 8 nm or less, 5 nm or less, 3 nm or less, or 1 nm or less. When the average size of the silicon crystals in the silicon / carbon composite matrix meets the above range, the stress intensity caused by the volume expansion of silicon can be reduced, thus improving the lifetime characteristics of the negative electrode active material. Furthermore, the average particle size of the silicon crystals meeting the above range can be attributed to the fact that Si-C bonds are preferred over Si-Si bonds.

[0046] Meanwhile, since the carbon-silicon / carbon composite material includes a silicon / carbon composite matrix, the silicon content can be 20 to 70% by weight, preferably 25 to 65% by weight, based on the total weight of the carbon-silicon / carbon composite material. Based on the total weight of the carbon-silicon / carbon composite material, if the silicon content is less than 20% by weight, the capacity may decrease, and if the silicon content exceeds 70% by weight, the problem caused by the volume expansion of silicon during charge and discharge cannot be solved, leading to structural damage and deterioration of the cycle characteristics of the negative electrode material.

[0047] Furthermore, based on the total weight of the carbon-silicon / carbon composite material, the silicon / carbon composite matrix can be present in an amount of 10 to 90% by weight, preferably 15 to 85% by weight. Based on the total weight of the carbon-silicon / carbon composite material, if the silicon / carbon composite matrix is ​​present in an amount of less than 10% by weight, the capacitance may decrease, and if the silicon / carbon composite matrix exceeds 90% by weight, the problem caused by the volume expansion of silicon during charge and discharge cannot be resolved, leading to structural damage and deterioration of the cycle characteristics of the anode material.

[0048] Meanwhile, silicon can be crystalline or amorphous, preferably amorphous or similar phases. When silicon is crystalline, the smaller the grain size, the denser the composite matrix can be, thus increasing the matrix strength to prevent cracking. Therefore, the initial efficiency or cycle life characteristics of the secondary battery can be improved.

[0049] Silicon can also include silicon oxide. Silicon oxide can be produced by the general formula SiO. x (0.5≤x≤2) indicates that when x is less than 0.5, expansion and contraction may increase during the charging and discharging process of the secondary battery, potentially deteriorating its lifespan characteristics. When x exceeds 2, inactive oxides increase, thus potentially reducing the initial efficiency of the secondary battery.

[0050] The content of silicon oxide in silicon can be 50% by weight or less relative to the total weight of silicon. If the content of silicon oxide in silicon exceeds 50% by weight, the initial efficiency of the secondary battery may decrease.

[0051] Meanwhile, the carbon-silicon / carbon composite material can have a c / a peak ratio of 0 to 1.5, preferably 0 to 1.3, more preferably 0 to 1.2, even more preferably 0 to 1.18, and even more preferably 0 to 1.15. When the c / a peak ratio of the carbon-silicon / carbon composite material meets the above range, it is more conducive to achieving the purpose of the present invention, for example, because it exhibits the effect of maintaining stable electrochemical performance during lifetime assessment. Here, the c / a peak ratio represents the peak ratio between crystalline (c) and amorphous (a).

[0052] Methods for preparing carbon-silicon / carbon composite materials According to one embodiment of the present invention, a carbon-silicon / carbon composite material is prepared by the following preparation method: the preparation method includes forming a silicon / carbon composite matrix on the surface and within the pores of a porous carbon support to prepare a carbon-silicon / carbon composite material.

[0053] Meanwhile, according to one embodiment of the present invention, prior to the step of preparing carbon-silicon / carbon composite material, the preparation method may further include: (1) synthesizing asphalt by pyrolysis and polycondensation of petroleum-based raw materials; (2) curing and granulating the asphalt to obtain granular asphalt, or curing, granulating and pulverizing the asphalt to obtain powdered asphalt; (3) stabilizing the granular asphalt or powdered asphalt; (4) carbonizing the stabilized asphalt to obtain carbonized products; and (5) activating the carbonized products to obtain porous carbon carriers.

[0054] The following describes the steps of a method for preparing carbon-silicon / carbon composite materials according to one embodiment of the present invention.

[0055] Step (1) In step (1), asphalt can be synthesized by pyrolysis and condensation of petroleum-based raw materials.

[0056] In specific embodiments of the present invention, the petroleum-based feedstock may include at least one selected from the group consisting of: pyrolysis fuel oil (PFO), naphtha cracking bottom oil (NCB), ethylene cracking bottom oil (EBO), vacuum residue (VR), deasphalted oil (DAO), atmospheric residue (AR), RFCC-DO, fluidized bed catalytic cracking decanter oil (RFCC-DO), and heavy aromatics oil. In a preferred embodiment of the present invention, the petroleum-based feedstock may include pyrolysis fuel oil.

[0057] In specific embodiments of the present invention, the petroleum-based raw material may include 10 to 90% by weight of aromatic compounds. Preferably, the petroleum-based raw material may include 20 to 80% by weight, and more preferably 30 to 70% by weight of aromatic compounds. When the content of aromatic compounds in the petroleum-based raw material meets the above range, even without separately pulverizing the solid asphalt particles, a porous carbon support with controlled pore characteristics can be obtained by stabilizing, carbonizing, and activating the solid asphalt particles, wherein the solid asphalt particles will be described below.

[0058] In specific embodiments of the present invention, the aromatic compound may be a compound having one to four aromatic rings. Specifically, the aromatic compound may include at least one selected from the group consisting of substituted or unsubstituted benzene, naphthalene, phenanthrene, indene, biphenyl, anthracene, tetrahydronaphthalene, and fluorene. In this case, even without separately pulverizing the solid asphalt granules, a porous carbon support with controlled pore characteristics can be obtained by stabilizing, carbonizing, and activating the solid asphalt granules, which will be described below.

[0059] In a specific embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out at a temperature of 350°C to 500°C. In a preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out at a temperature of 400°C to 500°C. In a more preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out at a temperature of 430°C to 470°C. When the pyrolysis and polycondensation temperature of petroleum-based raw materials is 350°C to 500°C, asphalt containing a relatively large amount of low molecular weight components can be generated. During the activation process in step (5), the low molecular weight components are first vaporized, thereby fully forming mesopores in the carbon support, wherein step (5) will be described below. If the pyrolysis and polycondensation temperature of petroleum-based raw materials is below 350°C, it is difficult to prepare asphalt that is solid at room temperature. If the temperature exceeds 500°C, the asphalt contains a relatively large amount of high molecular weight components, and therefore it is difficult to prepare a carbon support with mesopores.

[0060] In specific embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out in an atmosphere of an oxidizing gas, an inert gas, or a mixture thereof. In a preferred embodiment of the present invention, the oxidizing gas can be oxygen, ozone, or a combination thereof, the inert gas can be nitrogen, helium, neon, argon, or a combination thereof, and the mixed gas can be air, but the present invention is not particularly limited thereto.

[0061] Using oxidizing gases in the pyrolysis and polycondensation of petroleum-based feedstocks can produce asphalt with a high softening point, but it is difficult to carry out pyrolysis and polycondensation at high temperatures. Using inert gases in the pyrolysis and polycondensation of petroleum-based feedstocks allows for high-temperature pyrolysis and polycondensation, but it is difficult to prepare asphalt with a relatively high softening point. When a mixture of oxidizing and inert gases is used in the pyrolysis and polycondensation of petroleum-based feedstocks, pyrolysis and polycondensation can be carried out at relatively high temperatures to produce asphalt with a relatively high softening point.

[0062] In a specific embodiment of the present invention, the gas can be supplied at a flow rate of 10 to 800 mL / min during the pyrolysis and polycondensation of petroleum-based feedstocks. In a preferred embodiment of the present invention, the gas can be supplied at a flow rate of 100 to 500 mL / min during the pyrolysis and polycondensation of petroleum-based feedstocks. When the flow rate of the gas is less than 10 mL / min, the asphalt yield increases, but the amount of low molecular weight components becomes excessive, which is detrimental to subsequent processing such as stabilization. When the flow rate of the gas exceeds 800 mL / min, the asphalt yield decreases.

[0063] In specific embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out for 1 to 10 hours. In a preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out for 2 to 8 hours. In a more preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based raw materials can be carried out for 2 to 7 hours. If the pyrolysis and polycondensation time of petroleum-based raw materials is less than 1 hour, it is difficult to prepare asphalt with a high softening point; if it exceeds 10 hours, there is a possibility of excessive formation of quinoline-insoluble components.

[0064] In a specific embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out under stirring. The stirring conditions for the petroleum-based feedstocks are not particularly limited; for example, a stirrer rotating at 10 to 500 rpm can be used.

[0065] In a specific embodiment of the present invention, the asphalt synthesized in step (1) may have a softening point of 200°C to 350°C. In a preferred embodiment of the present invention, the asphalt may have a softening point of 200°C to 330°C. In a more preferred embodiment of the present invention, the asphalt may have a softening point of 200°C to 300°C. Because the asphalt prepared according to the present invention has a high softening point, when used as a precursor for preparing a carbon support, the stabilization process is easy, and a high yield can be obtained after carbonization and activation.

[0066] In a specific embodiment of the present invention, the yield of asphalt synthesized in step (1) can be 10 to 50% by weight. In a preferred embodiment of the present invention, the yield of asphalt can be 10 to 40% by weight. In a more preferred embodiment of the present invention, the yield of asphalt can be 20 to 30% by weight.

[0067] In a specific embodiment of the present invention, a pretreatment step can be performed on the petroleum-based raw material before step (1). By removing the low-boiling-point components contained in the petroleum-based raw material through the pretreatment step, asphalt with a higher softening point can be prepared.

[0068] In a specific embodiment of the present invention, the pretreatment step can be carried out at a temperature equal to or lower than that of the pyrolysis and polycondensation of the petroleum-based raw material in step (1), but is not particularly limited to this condition. Specifically, the pretreatment step can be carried out at 250 to 450°C, preferably at 250 to 400°C, and more preferably at 300 to 400°C.

[0069] In a specific embodiment of the present invention, the pretreatment step may be carried out for a time equal to or less than that of the pyrolysis and polycondensation of the petroleum-based raw material in step (1), but is not particularly limited to this condition. Specifically, the pretreatment step may be carried out for 1 to 8 hours, preferably 1 to 6 hours, and more preferably 1 to 5 hours.

[0070] In addition, in step (2), asphalt can be cured and granulated to obtain granular asphalt, or asphalt can be cured, granulated and crushed to obtain powdered asphalt.

[0071] First, in the case of granulated asphalt, the asphalt (liquid) obtained in step (1) is solidified, for example, by extrusion and cooling, and granulated to the desired size to obtain solid asphalt aggregate (granulated asphalt). The process of obtaining solid asphalt aggregate by extruding, cooling, and granulating liquid asphalt can be carried out using commercially available equipment. For example, this process can be carried out using a double-belt cooler and flaper manufactured by IPCO, but the present invention is not particularly limited to this equipment.

[0072] The asphalt aggregate (granular asphalt) obtained in step (2) has an average particle size of 1 to 30 mm, preferably 5 to 25 mm. When the average particle size of the asphalt aggregate (granular asphalt) is within this range, a porous carbon support can be prepared by stabilization, carbonization, and activation as described later, without separately crushing the asphalt aggregate (granular asphalt).

[0073] In the case of powdered asphalt, the asphalt aggregate (granular asphalt) can be further crushed or pulverized and classified. The asphalt aggregate (granular asphalt) can be further micronized by crushing or pulverizing, and its particle size distribution can be made more uniform by classification. Classification can be performed using dry classification, wet classification, or classification using sieves. By crushing or pulverizing and classifying, powdered asphalt with an average particle size of 50 to 500 μm can be obtained.

[0074] In step (3), a step of stabilizing granular asphalt or powdered asphalt may be performed.

[0075] First, the granular or powdered asphalt obtained in step (2) is subjected to preliminary oxidation to stabilize the carbon structure of the asphalt.

[0076] In a specific embodiment of the present invention, stabilization can be carried out in an oxidizing gas atmosphere. In a preferred embodiment of the present invention, stabilization can be carried out in an air atmosphere, but the present invention is not particularly limited thereto.

[0077] In a specific embodiment of the invention, stabilization can be carried out at a temperature of 100°C to 500°C, preferably 150°C to 300°C. When stabilization is carried out at this temperature, the carbon structure in the granular or powdered asphalt changes from thermoplastic to thermosetting, allowing this structure to be stably maintained during subsequent carbonization. In this case, the heating rate can be 2 to 10°C / min. If the heating rate is too slow, the productivity may be poor, while if the heating rate is too fast, it may be difficult to achieve uniform stabilization.

[0078] In a specific embodiment of the invention, stabilization can be carried out at a pressure of 0.1 to 10 bar, preferably 0.5 to 5 bar. When stabilization is carried out at this pressure, even the carbon structure inside granular or powdered asphalt can be sufficiently stabilized.

[0079] In a specific embodiment of the invention, stabilization can be carried out under conditions of an oxidizing gas, preferably air, with a flow rate of 0.1 to 500 mL / min, more preferably 1 to 300 mL / min. When stabilization is carried out under these oxidizing gas flow rate conditions, even the carbon structure inside granular or powdered asphalt can be sufficiently stabilized.

[0080] In a specific embodiment of the invention, stabilization can be performed for 1 to 10 hours, preferably 2 to 8 hours. By performing stabilization for this period of time, even the carbon structure inside granular or powdered asphalt can be sufficiently stabilized.

[0081] In step (4), the stabilized asphalt is carbonized to obtain carbonized products. By carbonizing the stabilized asphalt, other functional groups included in the asphalt can be removed, resulting in carbonized products that are essentially composed of pure carbon.

[0082] In a specific embodiment of the present invention, carbonization can be carried out under an inert gas atmosphere. In a preferred embodiment of the present invention, carbonization can be carried out under a nitrogen or argon atmosphere, but the present invention is not particularly limited thereto.

[0083] In a specific embodiment of the invention, carbonization can be carried out at a temperature greater than 700°C and equal to or less than 1000°C, preferably 800°C to 900°C. If the carbonization temperature is below this range, carbonization cannot be sufficiently carried out; if the carbonization temperature is above this range, the carbonization yield may decrease.

[0084] In a specific embodiment of the invention, carbonization can be carried out under conditions of an inert gas, preferably nitrogen, with a flow rate of 0.1 to 30 mL / min, more preferably 0.1 to 10 mL / min. When carbonization is carried out under these inert gas flow rate conditions, the stabilized asphalt can be fully carbonized.

[0085] In a specific embodiment of the present invention, carbonization can be carried out for 0.5 to 5 hours, preferably 1 to 3 hours. When carbonization is carried out for this period of time, the stabilized asphalt can be fully carbonized.

[0086] In step (5), the carbonization product is activated to obtain a porous carbon support. By activating the carbonization product, pores are formed in the carbonization product, thereby obtaining a porous carbon support.

[0087] In a specific embodiment of the present invention, the activation of the carbonization product can be carried out under an oxidizing gas atmosphere. In a preferred embodiment of the present invention, the activation of the carbonization product can be carried out under a vapor atmosphere, but the present invention is not particularly limited thereto.

[0088] In a specific embodiment of the present invention, the activation of the carbonization product can be carried out at a temperature greater than 700°C and equal to or less than 1000°C, preferably 800°C to 900°C. When the carbonization product is activated at this temperature, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.

[0089] In a specific embodiment of the present invention, the activation of the carbonization product can be carried out at a pressure of 0.1 to 10 bar, preferably 0.1 to 5 bar. When the carbonization product is activated at this pressure, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.

[0090] In a specific embodiment of the present invention, the activation of the carbonization product can be carried out under conditions of an oxidizing gas, preferably a vapor, with a flow rate of 0.1 to 100 mL / min, more preferably 0.1 to 50 mL / min. When the carbonization product is activated under these oxidizing gas flow rate conditions, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.

[0091] In a specific embodiment of the present invention, the activation of the carbonized product can be carried out for 0.5 to 5 hours, preferably 1 to 3 hours. By activating the carbonized product for this period of time, a porous carbon support with sufficient micropores and mesopores can be obtained.

[0092] In a specific embodiment of the present invention, the stabilization, carbonization, and activation in steps (3) to (5) can each be performed in a microwave-heated furnace. In a preferred embodiment of the present invention, the stabilization, carbonization, and activation in steps (3) to (5) can all be performed in a microwave-heated furnace. A microwave-heated furnace is preferred because it can raise the temperature of the asphalt itself without raising the external temperature of the asphalt, but the present invention is not particularly limited thereto.

[0093] In a specific embodiment of the present invention, steps (3) to (5) can be performed continuously in one device. In a preferred embodiment of the present invention, steps (3) to (5) can be performed continuously in a rotary kiln, but the present invention is not particularly limited to this device. Since steps (3) to (5) are performed continuously in one device, process optimization can be achieved.

[0094] In a specific embodiment of the present invention, the porous carbon support obtained in step (5) can be further crushed or pulverized and classified. The porous carbon support can be further micronized by crushing or pulverizing, and the particle size distribution of the porous carbon support can be made uniform by classification. Here, classification can be carried out by dry classification, wet classification, or classification using a sieve. By crushing or pulverizing and classifying, an average particle size of 1 to 20 μm and a BET specific surface area of ​​300 to 3000 m² can be obtained. 2 Porous carbon support powder with a tap density of 0.05 to 0.5 g / mL. Furthermore, based on the total pore volume, the porous carbon support powder has a mesopore volume ratio of 5% to 80%, wherein the mesopores have a pore size of 2 to 50 nm.

[0095] Meanwhile, when there is no additional pulverization of the asphalt in step (2) followed by stabilization, carbonization and activation of the granular asphalt to obtain a porous carbon carrier, the carbon carrier can be pulverized (or additionally graded) to have an average particle size of 1 to 20 μm, but the present invention is not limited thereto.

[0096] Next, a silicon / carbon composite matrix is ​​formed on the surface and inside the pores of the porous carbon support to prepare a carbon-silicon / carbon composite material.

[0097] In this context, the formation of the silicon / carbon composite matrix can be performed using equipment (e.g., a rotary kiln) and methods (e.g., chemical vapor deposition (CVD)) known in the art. Specifically, a silicon / carbon composite matrix can be formed on the surface and within the pores of a porous carbon support by performing composite CVD, wherein the composite CVD is performed by simultaneously supplying a silicon source and a carbon source to the porous carbon support.

[0098] In specific embodiments of the present invention, the silicon source may include at least one selected from silane (SiH4), dichlorosilane (SiH2Cl2), silicon tetrafluoride (SiF4), silicon tetrachloride (SiCl4), methylsilane (CH3SiH3), and disilane (Si2H6), but the present invention is not particularly limited thereto.

[0099] In addition, the carbon source may include at least one selected from the group consisting of methane, ethane, propane, butane, methanol, ethanol, propanol, propylene glycol, butane glycol, ethylene, propylene, butene, butadiene, cyclopentene, acetylene, benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene and dibutylhydroxytoluene, but the present invention is not particularly limited thereto.

[0100] Furthermore, composite CVD can be performed at temperatures ranging from 300°C to 600°C, preferably from 450°C to 550°C. Additionally, composite CVD can be performed at atmospheric pressure, or, if necessary, at a low vacuum of approximately 10 Torr. Furthermore, in composite CVD, based on feed batches of 10g to 100g, the silicon source can be supplied at a feed flow rate of 100sccm to 1000sccm, and the silicon and carbon sources can be supplied at a weight ratio of 1:0.1 to 1:2, preferably 1:0.15 to 1:1.9.

[0101] If the weight ratio of silicon source to carbon source exceeds 1:2 (silicon source less than 1, carbon source greater than 2), a relatively large amount of SiCx may be formed, resulting in reduced capacity and cycle characteristics. If the weight ratio is less than 1:0.1 (silicon source greater than 1, carbon source less than 0.1), a relatively small amount of SiCx will be formed, and a relatively large amount of Si may be formed. Therefore, the problem caused by the volume expansion of silicon during charge and discharge cannot be solved, which leads to structural damage to the anode material.

[0102] Negative electrode active materials According to another embodiment of the present invention, a negative electrode active material is provided, which includes a carbon-silicon / carbon composite material.

[0103] The negative electrode active material according to one embodiment of the present invention may include a carbon-silicon / carbon composite material.

[0104] In addition to carbon-silicon / carbon composite materials, the negative electrode active materials of the embodiments of the present invention may also include carbon-based negative electrode materials, specifically, graphite-based negative electrode materials. For example, the negative electrode active material can be obtained by mixing the carbon-silicon / carbon composite material according to the embodiments of the present invention with a carbon-based negative electrode material, such as a graphite-based negative electrode material.

[0105] Here, carbon-based anode materials may include, for example, at least one selected from the group consisting of: natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon, carbon fiber, carbon nanotubes, pyrolytic carbon, coke, calcined organic polymers and carbon black, but are not particularly limited thereto.

[0106] Relative to the total weight of the negative electrode active material, the content of carbon-based negative electrode material in the negative electrode active material according to the embodiments of the present invention can be 2 to 80% by weight, preferably 5 to 70% by weight, and more preferably 30 to 70% by weight.

[0107] The negative electrode active material according to embodiments of the present invention can be effectively used to manufacture the negative electrode of a secondary battery, specifically, it can be used to manufacture the negative electrode of a lithium secondary battery and the negative electrode of an all-solid-state battery.

[0108] All-solid-state batteries According to another embodiment of the present invention, an all-solid-state battery is provided, which includes an SEI (solid electrolyte interface) layer comprising a carbon-silicon / carbon composite material.

[0109] The all-solid-state battery may be an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte between the positive electrode and the negative electrode. The negative electrode may include a negative electrode active material layer, wherein at least a portion of the negative electrode active material particles in the negative electrode active material layer may include an SEI (solid electrolyte interface) layer, and the SEI (solid electrolyte interface) layer includes the aforementioned carbon-silicon / carbon composite material.

[0110] Meanwhile, the negative electrode active material particles can be carbon-based negative electrode materials. In this case, the content can be the same as the above-mentioned content regarding negative electrode active materials, so the relevant explanation is omitted.

[0111] In addition, apart from the negative electrode active material particles and SEI layer of the all-solid-state battery, the negative electrode structure, positive electrode structure and solid electrolyte structure can adopt the known structures of all-solid-state batteries, and therefore are not particularly limited in this invention.

[0112] Specific ways of implementing the present invention Example The invention will be described in more detail below through examples. These examples are for illustrative purposes only, and the scope of the invention is not limited thereto.

[0113] <Example 1> 300g of petroleum-based residue oil (YNCC, HTC PFO (pyrolysis fuel oil)) was loaded into a reactor equipped with a stirrer. Pyrolysis and polycondensation were carried out at 450°C for 3 hours while nitrogen was supplied at a flow rate of 100mL / min. During this time, the stirrer was rotated at 200rpm to mix the reactants (step (1)). The polymerized asphalt was then solidified and granulated to obtain solid asphalt granules with an average particle size of 1 to 30mm.

[0114] The solid asphalt aggregate obtained above was crushed to prepare asphalt particles with an average particle size of 200 μm (step (2)). Then, it was introduced into a rotary kiln with three zones for stabilization (step (3)), carbonization (step (4)), and activation (step (5)) in sequence. The conditions for stabilization, carbonization, and activation are shown in Table 1 below.

[0115] The specific surface area of ​​the carbon support was measured using a Belserp mini II according to ASTM D4820-93. The tap density of the carbon support was measured using an Electrolab (ETD-1020x) according to ASTM B527. The average particle size of the carbon support was measured using a Horiba laser particle analyzer (LA-960V2) according to ASTM E112. The results are shown in Table 1.

[0116] [Table 1]

[0117] The porous carbon support of the reference example was pulverized using a pulverizer (NETZSCH, air jet mill) to obtain micronized porous carbon support with an average particle size of 7 μm. Next, 15 g of the micronized porous carbon support was fed into a rotating CVD apparatus and heated to 475 °C under an inert atmosphere (N2). Composite CVD was then performed for 1 hour at a gas flow rate of SiH4:C2H4 = 450 sccm:144 sccm (the gas flow rate ratio of silicon source to carbon source was 1:0.32). This formed a silicon / carbon composite matrix on the surface and within the pores of the porous carbon support, thus preparing a carbon-silicon / carbon composite material.

[0118] <Example 2> The gas flow rate of SiH4:C2H4 = 450 sccm:144 sccm was changed to SiH4:C2H4 = 450 sccm:108 sccm (the gas flow rate ratio of silicon source to carbon source is 1:0.24). Otherwise, the carbon-silicon / carbon composite material was prepared in the same manner as in Example 1.

[0119] <Example 3> The gas flow rate of SiH4:C2H4=450sccm:144sccm was changed to SiH4:C2H4=150sccm:450sccm (the gas flow rate ratio of silicon source to carbon source is 1:3), and the carbon-silicon / carbon composite material was prepared in the same manner as in Example 1.

[0120] <Comparative Example> Carbon-silicon / carbon composite materials were prepared in the same manner as in Example 1, except that instead of composite CVD, deposition was performed for 1 hour at a SiH4 gas flow rate of 450 sccm and a temperature of 475°C, followed by deposition for 1 hour at a C2H4:Ar gas flow rate of 100 sccm:900 sccm and a temperature of 700°C.

[0121] <Experimental Example 1> (1) Scanning electron microscopy (SEM) analysis The carbon-silicon / carbon composite material prepared according to Example 1 was observed using scanning electron microscopy (SEM). The results of the SEM analysis are shown in... Figure 1 middle.

[0122] The results confirmed that, Figure 1 As shown, a uniform silicon / carbon composite matrix is ​​formed on the surface of the porous carbon support and throughout the interior of the pores.

[0123] (2) Electrochemical evaluation Half-coin batteries were fabricated using the composite materials from Examples 1, 2, 3, and the comparative example, and electrochemical evaluations were performed. The fabrication conditions for the half-coin batteries are shown in Table 2, and the evaluation results are shown in Tables 3 and 4. Figure 2 As shown in Table 2, AM, CM, and BM represent active materials (carbon-silicon / carbon composites), conductive materials (Super P carbon black), and binders (styrene-butadiene rubber / carboxymethyl cellulose, 5:5), respectively. EC, EMC, DMC, FEC, VC, and PS represent ethylene carbonate, methyl ethyl carbonate, dimethyl carbonate, fluoroethylene carbonate, vinylene carbonate, and propane sulpholactone, respectively.

[0124] [Table 2]

[0125] [Table 3]

[0126] [Table 4]

[0127] As shown in Tables 3 and 4, and Figure 2 As shown, Examples 1 and 2 exhibited a reversible capacity of approximately 2000 mAh / g, a very low peak near 0.45 V, and achieved a high cycle retention (CE) of 99.6% or higher after 25 cycles. The peak near 0.45 V indicates the suSi phase. In contrast, in Example 3, the gas flow ratio of silicon to carbon source during the composite CVD process was 1:3, which exceeded the specified range. The results confirmed that carbon was more dominant than silicon in the silicon / carbon composite matrix, thus reducing the capacity and exhibiting a lower ICE. The results also confirmed that in the comparative examples, silicon and carbon did not form a composite matrix that was bonded to each other, resulting in a significantly reduced cycle retention.

[0128] (3) dQ / dV measurement (measurement related to c-LiSi phase) Regarding Examples 1, 2, and Comparative Example 1, formation (CC-CV) was performed using a C-rate calculated based on the Si loading of the anode material, under conditions of 0.1C-0.1C and 0.005V / 0.01C cutoff (CV). Then, dQ / dV (d(Q-Qo) / dE) was obtained using the collected data. In this invention, dQ / dV was calculated and obtained using the EC-Lab analysis method. The results are as follows... Figure 3 As shown.

[0129] As a result, the c / a peak ratio of Example 1 was 0.66, the c / a peak ratio of Example 2 was 0.64, and the c / a peak ratio of the comparative example was 2.72. The results confirm that, compared to Comparative Example 1, Examples 1 and 2 formed less c-LiSi phase; therefore, stable electrochemical performance is expected to be maintained during lifetime evaluation.

[0130] (4) XRD analysis For the carbon-silicon / carbon composite material of Example 1, XRD analysis was performed under the following conditions. The results are shown below. Figure 4 middle.

[0131] Equipment: D-MAX 2200 (RIGAKU) Angle: 20-70° Sampling W: 0.01 X-ray: 40kV / 30mA DivSlit: 1 / 2 degree DivH.L.Slit: 10mm SctSlit: 1 / 2 degree RecSlit: 0.15 mm The results confirmed that the carbon-silicon / carbon composite material of Example 1 had no Si crystallization peak or SiC peak.

[0132] <Examples 1-1 to 1-3> The composite material according to Example 1 was heat-treated at temperatures of 600°C (Example 1-1), 700°C (Example 1-2), and 900°C (Example 1-3), respectively.

[0133] Experimental Example 2 (1) XRD analysis XRD analysis was performed on the composite materials according to Example 1, Examples 1-1 to 1-3 and the comparative example.

[0134] Specifically, XRD analysis was performed on the composite material of Example 1, the heat-treated composite materials of Examples 1-1 to 1-3, and the composite material of the comparative example under the following conditions. The results are shown in... Figure 5 middle.

[0135] Equipment: D-MAX 2200 (RIGAKU) Angle: 20-70° Sampling W: 0.01 X-ray: 40kV / 30mA DivSlit: 1 / 2 degree DivH.L.Slit: 10mm SctSlit: 1 / 2 degree RecSlit: 0.15 mm The results show that, in the case of the comparative example, due to the additional carbon coating formed at a temperature of 700°C, a crystalline Si peak was clearly observed, and it can be seen that, as mentioned above, poor results were obtained in the lifetime evaluation.

[0136] Furthermore, in the case of heat-treated composite materials, no obvious Si or SiC peaks were observed for heat treatment at temperatures up to 700°C, and a broad amorphous peak was observed between 28° and 32°.

[0137] Furthermore, during heat treatment at 900℃, SiC(111), SiC(220), and Si(111) peaks were observed. The grain size was then calculated using these peaks, yielding the following results.

[0138] SiC(111): 1.1 nm SiC(220): 2.4 nm Si(111): 4.8 nm Based on the above results, it can be confirmed that a silicon / carbon composite matrix was formed on a porous carbon support, thereby controlling the Si grain size.

[0139] Although exemplary embodiments of the present invention have been described above, the spirit of the invention is not limited to the embodiments provided herein. Those skilled in the art will understand that various other embodiments can be readily proposed within the scope of the same inventive concept by adding, modifying, deleting, or supplementing components, and such embodiments should also fall within the scope of the present invention.

Claims

1. A carbon-silicon / carbon composite material, comprising: A porous carbon support, based on total pore volume, having a mesopore volume ratio of 5% to 80%, wherein the mesopores have a pore size of 2 nm to 50 nm; and A silicon / carbon composite matrix, wherein the silicon / carbon composite matrix is ​​disposed on the surface and within the pores of the porous carbon support.

2. The carbon-silicon / carbon composite material according to claim 1, wherein, The porous carbon support has the following characteristics: 300m 2 / g to 3000m 2 BET specific surface area per g Tap density from 0.05 g / mL to 0.5 g / mL, and Average particle size from 1 μm to 20 μm.

3. The carbon-silicon / carbon composite material according to claim 1, wherein, Based on the total weight of the carbon-silicon / carbon composite material, the silicon content is from 20% to 70% by weight.

4. The carbon-silicon / carbon composite material according to claim 1, wherein, Based on the total weight of the carbon-silicon / carbon composite material, the silicon / carbon composite matrix is ​​present in an amount of 10% to 90% by weight.

5. The carbon-silicon / carbon composite material according to claim 1, wherein, The average size of the silicon crystals in the silicon / carbon composite matrix is ​​10 nm or smaller.

6. The carbon-silicon / carbon composite material according to claim 1, wherein, The carbon-silicon / carbon composite material has a c / a peak ratio of 0 to 1.

5.

7. A method for preparing carbon-silicon / carbon composite materials, the method comprising: A silicon / carbon composite matrix is ​​formed on the surface and inside the pores of a porous carbon support to prepare carbon-silicon / carbon composite materials.

8. The method according to claim 7, wherein, Prior to the preparation of the carbon-silicon / carbon composite material, the following steps are also included: (1) Asphalt is synthesized by pyrolysis and condensation of petroleum-based raw materials; (2) Curing and granulating asphalt to obtain granular asphalt, or curing, granulating and crushing asphalt to obtain powdered asphalt; (3) Stabilize the granular asphalt or the powdered asphalt; (4) Carbonize the stabilized asphalt to obtain carbonization products; and (5) The carbonized product is activated to obtain a porous carbon support.

9. The method according to claim 7, wherein, The silicon / carbon composite matrix is ​​formed by composite CVD of silicon and carbon sources on the porous carbon support.

10. The method according to claim 9, wherein, The gas flow rate ratio of the silicon source to the carbon source is from 1:0.1 to 1:

2.

11. A negative electrode active material, comprising a carbon-silicon / carbon composite material according to any one of claims 1 to 6.

12. An all-solid-state battery, comprising an SEI (solid electrolyte interface) layer, said SEI layer comprising a carbon-silicon / carbon composite material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for manufacturing activated carbon

    KR1020190093960A

  • Mass production system of highly aromatic petroleum pitch

    US4242196A

  • Method for thermal cracking of heavy petroleum oil

    US4340464A